EOR additives from local sources - Awang, Mariyamni; Wan Abdul Rahman, Wan Aizan (2005)
This study investigates on how to reduce the cost of chemical additives by producing the chemicals locally and using as much local sources as possible. The detail discussions of this study is available in slides attached here.